2009
DOI: 10.5424/fs/2009183-01073
|View full text |Cite
|
Sign up to set email alerts
|

Silvicultural characterization of single-species stands of black pine in Catalonia (Spain)

Abstract: This study presents a silvogenetic typology of single-species stands of Pinus nigra in Catalonia (NE of Spain) based on the information supplied by the Second National Forest Inventory. Results of factor analysis applied to dendrometric variables show nine different stand types, identified mainly from variables related to diameter distribution and stand stocking. The character of uneven-aged stands, present in five of the groups though with different features, was analyzed using a truncated Weibull distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In our study area, for example, we found higher pine seedlings in stands with a high presence of big trees (with dbh > 27.5 cm) but low basal area values. However, this type of mature moderately opened stand is fairly uncommon nowadays (Aunós et al, 2009) due to the generalized abandon of forest management that has led to active densification of the stands (Poyatos et al, 2003). These processes are relatively slow and have only recently reached density levels high enough to hinder pine recruitment, as indicated by the higher presence of pine saplings compared to young seedlings in the understory of the stands.…”
Section: Factors Behind Pine Retreatmentioning
confidence: 98%
See 1 more Smart Citation
“…In our study area, for example, we found higher pine seedlings in stands with a high presence of big trees (with dbh > 27.5 cm) but low basal area values. However, this type of mature moderately opened stand is fairly uncommon nowadays (Aunós et al, 2009) due to the generalized abandon of forest management that has led to active densification of the stands (Poyatos et al, 2003). These processes are relatively slow and have only recently reached density levels high enough to hinder pine recruitment, as indicated by the higher presence of pine saplings compared to young seedlings in the understory of the stands.…”
Section: Factors Behind Pine Retreatmentioning
confidence: 98%
“…These forests were intensively managed for timber harvesting and pasture grazing until the mid-20th century (Ruiz de la Torre, 2006), but from that point onwards the intensity of human practices decreased significantly (Vicente-Serrano et al, 2004). During the past few decades, just a few individual-tree selection cuttings affecting only the most vigorous and well-shaped trees have been conducted on these forests (Trasobares and Pukkala, 2004;Aunós et al, 2009) interventions and livestock grazing) has allowed the establishment of new cohorts of the dominant pine species, causing a generalized densification of the stands (DGCN, 2005) and a progressive process of colonization by late-successional tree species, mainly Quercus species (e.g., Urbieta et al, 2011;Carnicer et al, 2014;Vayreda et al, 2013).…”
Section: Introductionmentioning
confidence: 99%